Metabolic and structural hepatic changes in diabetes and intracerebral haemorrhage: Comparative study of lipid-lowering and antidiabetic drugs - O. Dyomshyna; H. Krynytska; V. Zhyliuk (Regulatory Mechanisms in Biosystems, 2026)
Type 2 diabetes is a major global health problem frequently accompanied by hepatic metabolic disturbances. An exper i mental model of streptozotocin-induced type 2 diabetes complicated by intracerebral haemorrhage was established in rats. Pha r macological correction was performed using rosuvastatin, metformin, or vitamin D. Liver morphology was assessed by histolo g ical examination, while lipid and biochemical parameters were evaluated using spectrometric methods. Streptozotocin-induced type 2 diabetes was associated with significant dysregulation of glucose metabolism, hepatic cholesterol and triglyceride levels, and aminotransferase activity. The addition of intracerebral haemorrhage resulted in pronounced macrovesicular steatosis, deter i oration of the hepatic lipid profile, diapedesis haemorrhage, perivascular oedema, and marked lymphocytic infiltration. Rosuvastatin demonstrated the most pronounced corrective effect, leading to near-complete regression of steatosis, normalisation of lipid parameters, prevention of necrotic and haemorrhagic changes, and restoration of lobular liver architecture. Metformin and vitamin D produced moderate improvements in hepatic morphology and lipid metabolism without full normalisation. Intracerebral haemorrhage markedly aggravates hepatic morphofunctional disturbances in streptozotocin-induced type 2 diabetes, promoting the development of macrovesicular steatosis. Among the agents investigated, rosuvastatin exhibited the greatest hepatoprotective potential, whereas metformin and vitamin D showed moderate corrective effects. These findings support diffe r entiated pharmacological approaches and suggest potential benefits of combination therapy in diabetic hepatopathy. From a research perspective, further work should focus on identifying effective combinations of the drugs studied in this experimental model.